Odpowiedzi

2010-03-09T13:57:05+01:00
2x²-4/x²-4x+4=(√2x-2)(√2x+2)/(x+2)² x=2/√2 i x=-2/√2 i x=-2
x²-4x+4=(x+2)²


x+2/3x-6 =-1(x-2)/3(x-2)=-1/3




b)x(do czwartej)-1/x(do czwartej)+2x(kwadrat)+1
x⁴-1/x⁴+2x²+1=(x²-1)(x²+1)/x²(x²+2)+1=(x²-1)(x²+1)/(x²+1)(x₂+2)=x²-1/x²+2 =
=(x-1)(x+1)/(x²+2)
x=1 i x=-1

4x(kwadrat)-4/x(kwadrat)+1=4x²-4/x²+1=(2x-2)(2x+2)/x²+1=(2x-2)(2x+2)(x-1)/(x+1)(x-1)=(2x-2)(2x+2)/x+1 x=1 i x=-1

c).x(kwadrat)-7x+12/x(kwadrat)-16=(x+4)(x+3)/(x-4)(x+4)=x+3/x-4
x(kwadrat)-7x+12=(x+4)(x+3) x=-4 i x=-3

5x-15/3x+12=5(x-3)/3(x+4) x=3 i x=-4